Deforestation and environmental policy: A DSGE approach - Rodrigo Mendes Pereira; Geraldo Sandoval Góes (Institute for Applied Economic Research (ipea), 2019)
This paper proposes an environmental DSGE model with deforestation of a tropical rain forest. The forest can be used to produce goods, but it also affects the well-being of the representative individual. Environmental policy is implemented with the taxation of the deforestation activity. We calibrate the model for the Brazilian economy, and show that it predicts a procyclical deforestation, and that a more stringent policy reduces the volatility of deforestation. Moreover, technological progress decreases the stock of forest, and it does so more intensely with a lenient environmental policy.
Keywords: E32; Q32; O13; 330; deforestation; real business cycle; environmental policy; DSGE